2015
DOI: 10.17957/jgiass/3.1.675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Planting Depth and Variety on Container Produced Potatoes

Abstract: Food security has become a crucial issue because of climate change, reduction of arable land, increasing population and frequent occurrence of natural disasters. The solution for many space-starved Zimbabwean gardeners is to grow their potatoes in sacks. However, there is a growing concern on this production method as possible yields are claimed to be as high as 30kg per plant yet some experienced container potato producers have had yields below 0.5 kg per plant. A study aimed at improving the yield of contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…On potato, results showed that significant increment in potato tuber fresh weight at 10 cm and 15 cm depth of Agria variety in compared with the other variety (Draga) which did not have any response (Laei et al, 2012). Also, a research paper showed that the diameter of tuber was influenced by planting depth and potato variety (Tanyaradzwa et al, 2015). In another study bout the effect of planting depth, it was found that planting depth at 20 cm produce high significance in total yield and marketable yield than other treatments (Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On potato, results showed that significant increment in potato tuber fresh weight at 10 cm and 15 cm depth of Agria variety in compared with the other variety (Draga) which did not have any response (Laei et al, 2012). Also, a research paper showed that the diameter of tuber was influenced by planting depth and potato variety (Tanyaradzwa et al, 2015). In another study bout the effect of planting depth, it was found that planting depth at 20 cm produce high significance in total yield and marketable yield than other treatments (Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%